The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fpls.2017.01853
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Optimizing of in Vitro Hormonal Combination for G × N15 Vegetative Rootstock Proliferation Using Artificial Neural Network-Genetic Algorithm (ANN-GA)

Abstract: The efficiency of a hybrid systems method which combined artificial neural networks (ANNs) as a modeling tool and genetic algorithms (GAs) as an optimizing method for input variables used in ANN modeling was assessed. Hence, as a new technique, it was applied for the prediction and optimization of the plant hormones concentrations and combinations for in vitro proliferation of Garnem (G × N15) rootstock as a case study. Optimizing hormones combination was surveyed by modeling the effects of various concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 48 publications
(53 reference statements)
6
27
0
Order By: Relevance
“…The pear rootstock responses to in vitro nutrients has been reported that varies with the macro-nutrients levels in the culture medium [10]. Comparison of our comprehensive results to the previous results [10, 15, 50, 51] showed for the first time that the concentrations of macro- and micro-nutrients depend highly on the concentrations of used hormones as their interaction could determine the quality of plantlets. Arab et al [15] predicted and maximized the number and length of in vitro regenerated shoots by decreasing NH 4 + concentration and optimizing NO 3 − concentration, simultaneously.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The pear rootstock responses to in vitro nutrients has been reported that varies with the macro-nutrients levels in the culture medium [10]. Comparison of our comprehensive results to the previous results [10, 15, 50, 51] showed for the first time that the concentrations of macro- and micro-nutrients depend highly on the concentrations of used hormones as their interaction could determine the quality of plantlets. Arab et al [15] predicted and maximized the number and length of in vitro regenerated shoots by decreasing NH 4 + concentration and optimizing NO 3 − concentration, simultaneously.…”
Section: Discussionsupporting
confidence: 66%
“…AI has recently been successfully and progressively applied in plant bio-researches [48] as well as for predicting the optimal plant tissue culture conditions [49] and media components [10, 15, 50, 51]. The in vitro plant tissues development is under control of the culture media nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Rumelhart et al ( 1986 ), error backpropagation feature was introduced, a process that finds the gradients of the neurons' weights to adjust them, from the last layer to the first one. ANNs can also be found in multiple applications for plant science, e.g., leaf area index calculation (Yuan et al, 2017 ), rootstock genetics (Arab et al, 2017 ) or disease detection (Pérez-Bueno et al, 2016 ). For this reason, a deep analysis of how these algorithms and their multiple parameter settings behave with hyperspectral data is desirable, as they arise as powerful tools for the varietal classification objective.…”
Section: Introductionmentioning
confidence: 99%